-3
-6.
-12 minus -6 is -6
A negative minus a negative turns the latter into a plus positive,for example -6 minus -3 would be :-6 ++ 3 = -3A minus negative always turns into a plus positive...To get more Specific:Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +yIf x > y the answer is negativeIf x = y the answer is zeroIf x < y the answer is positive
-6 minus -14 is 8.
-3-(-6) = 3
negative 9
-3
-6.
3 minus -6 is 9.
-12 minus -6 is -6
A negative minus a negative turns the latter into a plus positive,for example -6 minus -3 would be :-6 ++ 3 = -3A minus negative always turns into a plus positive...To get more Specific:Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +yIf x > y the answer is negativeIf x = y the answer is zeroIf x < y the answer is positive
-6 minus -14 is 8.
0 minus negative 6 is equal to 6.
negative 2 over 6
Negative 12 minus 3 plus 9 is equal to -6
0.